1999
DOI: 10.3354/meps177063
|View full text |Cite
|
Sign up to set email alerts
|

Species specific uptake of radio-labelled phytodetritus by benthic meiofauna from the Baltic Sea

Abstract: ABSTRACT:The diatom Skeletonema costatum is one of the dominant phytoplankton species during spring in the northern Baltic Sea. We followed the uptake of radio-labelled S costatum by all major meiofauna species in a laboratory experiment. The uptake of labelled diatom carbon varied greatly among major meiobenthic taxa and anlong species belonging to the same class or phylum. Both total uptake and uptake per unit biomass were by far highest in the ostracod Candona neglecta accounting for 4 6 % of the total meio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…Our rationale for studying taxon rather than species diversity are: (1) the taxonomic limitations of different meiofaunal groups, especially in tropical ecosystems (e.g., about 70% of meiofaunal harpacticoid copepods in these regions are new to science, De Troch, 2001); (2) food preferences and strategies within a specific meiofauna group are far from known. Species-specific food preferences are only documented for a few nematode (e.g., Moens, Verbeeck, de Maeyer, Swings, & Vincx, 1999;Ó lafsson, Modig, & van de Bund, 1999) and copepod species (e.g., Buffan-Dubau & Carman, 2000;De Troch, Steinarsdó ttir, Chepurnov, & Ó lafsson, 2005;Pace & Carman, 1996) and may imply that certain levels of productivity will be used in different ways, i.e., less or more intensive so certain segments of the productivity range will be characterised by lower or higher species diversity. The use of higher taxa may skew the resolution of the diversity trends, however, it is hard to say whether this would consequently result in a hump-shaped relationship between productivity and diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Our rationale for studying taxon rather than species diversity are: (1) the taxonomic limitations of different meiofaunal groups, especially in tropical ecosystems (e.g., about 70% of meiofaunal harpacticoid copepods in these regions are new to science, De Troch, 2001); (2) food preferences and strategies within a specific meiofauna group are far from known. Species-specific food preferences are only documented for a few nematode (e.g., Moens, Verbeeck, de Maeyer, Swings, & Vincx, 1999;Ó lafsson, Modig, & van de Bund, 1999) and copepod species (e.g., Buffan-Dubau & Carman, 2000;De Troch, Steinarsdó ttir, Chepurnov, & Ó lafsson, 2005;Pace & Carman, 1996) and may imply that certain levels of productivity will be used in different ways, i.e., less or more intensive so certain segments of the productivity range will be characterised by lower or higher species diversity. The use of higher taxa may skew the resolution of the diversity trends, however, it is hard to say whether this would consequently result in a hump-shaped relationship between productivity and diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, providing just diatom-based detritus may be responsible for the attenuated response of the nematode community. In addition, the size of diatom cells may limit the number of diatom-feeding nematodes that are large enough to consume the cells (Olafsson et al, 1999). However, with a small average cell radius of ca.…”
Section: Nematode Feeding Selectivitymentioning
confidence: 99%
“…For example, in subtidal areas, no inequivocal influence of phytoplankton sedimentation on the density and biomass of meiofaunal nematodes was found (HEIP ET AL, 1985, ÓLAFSSON ET AL, 1999. However, SCHRATZBERGER ET AL (2007) showed that populations of the nematode Spilophorella paradoxa that feed on fresh organic material exhibited temporal patterns in their abundance and size distribution.…”
Section: Multivariate Analysismentioning
confidence: 99%